DESIGN OF A CASCODE BIPOLAR JUNCTION TRANSISTOR (BJT) RADIO FREQUENCY (RF) AMPLIFIER CIRCUIT - Wardhana, Arief Wisnu; Winasis, Winasis; Priswanto, Priswanto (Transmisi: Jurnal Ilmiah Teknik Elektro, 2025)
The purpose of this research is to develop an audio   receiver amplifier circuit. The  amplifier consists of a cascode  amplifier which is turned into an  amplifier by adding two parallel  resonators. One parallel  resonator is placed at the input. Another parallel  circuit is used as a collector load. Parallel  circuit was employed because this device is intended for use only over a narrow frequency range. The tuned amplifier’s frequency was  734 . A spoiling resistor of magnitude was added in series with the tuned circuit’s inductor to reduce the sharpness of the resonant peak, resulting in a  bandwidth. The famous cascode configuration was employed to improve the high-frequency performance of this  amplifier. The Multisim simulation results of the circuit shows that it has performed according to the specification. It can be concluded that the designed circuit has successfully carried out his duty, in that only the frequencies of interest within the bandwidth are amplified. The circuit has been able to selects a particular range of frequencies (from a lower frequency of  up to an upper frequency of ), and rejects the other undesired frequencies. Thus, giving the tuned amplifier a bandwidth of . The peak voltage was achieved at frequency of  . Furthermore, the cascode configuration employed has effectively eliminates the most trouble source of high-frequency loss – the input Miller capacitance.